Association of Neo-Family History Score with pathological complete response, safety, and survival outcomes in patients with breast cancer receiving neoadjuvant platinum-based chemotherapy: An exploratory analysis of two prospective trials. (August 2021) - Xu, Yaqian; Lin, Yanping; Wang, Yaohui; Zhou, Liheng; Xu, Shuguang; Wu, Yifan; Peng, Jing; Zhang, Jie; Yin, Wenjin; Lu, Jinsong
Abstract: Background: Homologous recombination deficiency is associated with platinum-based chemosensitivity, whereas few studies reported the predictive value of family history of cancer for breast cancer in the neoadjuvant setting. This study aimed to construct a novel family history scoring system and to explore its association with clinical outcomes for patients with breast cancer receiving neoadjuvant platinum-based chemotherapy. Methods: This study included 262 patients with locally advanced breast cancer enrolled in the SHPD001 and SHPD002 trials from October 2013 to June 2018. The Neo-Family History Score (NeoFHS) was calculated according to cancer type, age at diagnosis, kinship, and number of affected relatives. Findings: Clinical tumor stage (p=0·048), estrogen receptor status (p=0·001), progesterone receptor status (p=0·036), human epidermal growth factor receptor 2 status (p=0·013), and molecular subtype (p=0·016) were significantly related to NeoFHS. NeoFHS could serve as an independent predictive factor of pathological complete response (pCR) (OR=2·262, 95% CI 1·159-4·414, p=0·017) and an independent prognostic factor of relapse-free survival (adjusted HR=0·305, 95% CI 0·102-0·910, p=0·033). Alopecia (p=0·001), nausea (p=0·001), peripheral neuropathy (p=0·018), diarrhea (p=0·026), constipation (p=0·037) of any grade and leukopenia of grade 3 or greater (p=0·005) were more common in patients with higher NeoFHS. Interpretation: NeoFHS is a practical and effective biomarker for predicting not only pCR and survival outcomes but also chemotherapy-induced adverse events for neoadjuvant platinum-based chemotherapy in breast cancer. It may help screen candidate responders and guide safety managements. Funding: Shanghai Natural Science Foundation [grant number 19ZR1431100], Clinical Research Plan of Shanghai Hospital Development Center [grant numbers SHDC2020CR3003A, 16CR3065B, and 12016231], Shanghai "Rising Stars of Medical Talent" Youth Development Program for Youth Medical Talents - Specialist Program [grant number 2018-15], Shanghai "Rising Stars of Medical Talent" Youth Development Program for Outstanding Youth Medical Talents [grant number 2018-16], Shanghai Collaborative Innovation Center for Translational Medicine [grant number TM201908], Multidisciplinary Cross Research Foundation of Shanghai Jiao Tong University [grant numbers YG2017QN49, ZH2018QNA42, and YG2019QNA28], Nurturing Fund of Renji Hospital [grant numbers PYMDT-002, PY2018-IIC-01, PY2018-III-15, and PYIII20-09], Science and Technology Commission of Shanghai Municipality [grant numbers 20DZ2201600 and 15JC1402700], and Shanghai Municipal Key Clinical Specialty.